Quantum chemical molecular dynamics simulation of carbon nanotube–graphene fusion. Issue 13 (2nd November 2017) - Qian, Hu-Jun; Eres, Gyula; Irle, Stephan
Abstract: Here we report a quantum mechanical molecular dynamics (QM/MD) study of a fusion process of an open-ended carbon nanotube on a graphene hole, which results in the formation of a so-called pillared graphene structure – a three-dimensional nanomaterial consisting entirely of sp 2 -carbons. The self-consistent-charge density-functional tight-binding potential was adopted in this study. Two different sizes of graphene holes with 12 or 24 central carbon atoms removed from a graphene flake, and a (6, 6) carbon nanotube with a compatible diameter were adopted. Formations of 6–7–6/5–8–5 defect structures were found on the fusion border between tube and graphene hole. The 6–7–6 structure was found to bear less curvature-induced strain energy and therefore to be more stable and much easier to form than the 5–8–5 structure.